Sustainable pathways : the role of indigenous tribes and native practices in India's economic model - Malhotra, Nishi (Emerald Publishing Limited, 2024)
Amid the vibrant culture and deep-rooted traditions of India thrive hundreds of Indigenous tribes and ethnic communities. However, these artisan groups find themselves on the fringes of the nation's financial system. Sustainable Pathways: The Role of Indigenous Tribes and Native Practices in India's Economic Model illuminates the struggles of these communities that live on the outskirts of mainstream Indian society and examines their journey to financial empowerment. Author Nishi Malhotra provides an in-depth exploration of India's Indigenous tribes, emphasizing their unique yet financially undervalued arts and crafts traditions. Highlighting initiatives that improve Indigenous economic participation, she critically addresses their financial exclusion and also underscores their vulnerabilities, despite their deep traditional knowledge and ecological insights. Contrasting Eastern and Western perspectives on Indigenous wisdom, Malhotra's discussion extends into a global context, advocating for educational and policy-making approaches that integrate Indigenous practices and philosophies into sustainability and conservation efforts. A crucial resource for scholars, students, and enthusiasts from fields as diverse as the social sciences, finance, and the arts, this work offers deep insights into the financial inclusion of Indigenous artisans in India.
Includes index.
Keywords: Indigenous peoples -- India -- Economic conditions.; Social Science -- Indigenous Studies.; Business ethics and social responsibility.; Indigenous peoples.; elektronické knihy; electronic books